Indigenous Religious Believers’ Experience to Manage Stigma in Indonesia - Wiwik Novianti; Mite Setiansah; Nana Sutikna; Kilau Riksaning Ayu (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2023)
The state acknowledges the existence of indigenous religious believers, yet given the social stigma since considered primitive, heresy, and even atheist. The stigma given to the indigenous religious believers negatively results in personal and social relationships eventually influencing the believers’ life aspects. Thus, the stigma management communication strategies of the believers are essential when interacting with other people in their environments. This research depicts how indigenous religious believers manage the stigma of living in society. It was conducted in Banyumas, Central Java, Indonesia. The 28 groups of believers were listed on Majelis Luhur Kepercayaan Terhadap Tuhan YME (MLKI) of Banyumas. The study used a phenomenological approach. The data were collected through in-depth interviews with 10 participants from some communities of believers. Seventeen years participants were selected using a snowball sampling technique. The researchers then classified them into some categories based on the predetermined themes. The research finding showed that stigma limited the believers’ interactions with non-believers. In responding to these stigmas, the believers developed different management communication strategies: accepting, denying by providing information, denying by discrediting the discreditor, avoiding, reducing offensiveness, and ignoring.